The under-reporting of energy intake influences the dietary pattern reported by obese women in the waiting list for bariatric surgery - Ravelli, Michele Novaes [UNESP]; Pereira Sartori, Maria Marcia [UNESP]; Corrente, Jose Eduardo [UNESP]; Rasera Junior, Irineu; Prada de Souza, Noa Pereira [UNESP]; Marques de Oliveira, Maria Rita [UNESP] (Pontificia Universidade Catolica Campinas, 2018)
Objective To verify the interference of the energy intake under-reporting in the determination of the dietary patterns and nutrient intakes reported by obese women in the waiting list for bariatric surgery. Methods The study included 412 women aged 20 to 45 years with a body mass index ranging from 35 to 60kg/m(2) who were on waiting list for bariatric surgery. Data from three reported food intake and physical activity, body weight, and height were used for estimating the reported energy intake, physical activity level, and resting energy expenditure. Subsequently, it was checked the biological plausibility of the reported energy intakes, classifying all participants as plausible reporters or under-reporters. Exploratory factor analysis was used to determine the participants' dietary patterns. The Mann-Whitney test assessed the reported energy and nutrient intakes between plausible reporters and under-reporters groups. The Z-test assessed the variables of plausible reporters or under-reporters in relation to all participants of the study. Results Six dietary patterns were determined for all participants of study. After excluding information from under-reporting women, only two dietary patterns remained similar to those of all participants, while three other dietary patterns presented different conformations from food subgroups to plausible reporters. The reported energy intake did not present difference for the subgroups of fruits, leaf vegetables and vegetables. However, the energetic value reported for the other food subgroups was higher for the plausible reporters. Conclusion The under-reporting of energy intake influenced the determination of dietary patterns of obese women waiting for bariatric surgery.
Keywords: Energy intake; Dietary pattern; Multivariate analysis; Obesity; Under-reporting